SCHOOL BOARD IMPROVEMENT PLANS IN RELATION TO THE AIP MODEL OF EDUCATIONAL ACCOUNTABILITY: A CONTENT ANALYSIS - van Barneveld, Christina; Stienstra, Wendy; Stewart, Sandra (Canadian Journal of Education/Revue canadienne de l'éducation, 2006)
For this study we analyzed the content of school board improvement plans in relation to the Achievement‐Indicators‐Policy (AIP) model of educational accountability (Nagy, Demeris, & van Barneveld, 2000). We identified areas of congruence and incongruence between the plans and the model. Results suggested that the content of the improvement plans, which contained a heavy emphasis on large‐scale, standardized assessments as a measure of student achievement, were incongruent with some key elements of the educational accountability model, especially as it related to the use of indicator data or policy information. Key words: educational planning, student achievement, large‐scale testing, student assessment L’étude présentée ici visait à analyser le contenu des plans de réussite des conseils scolaires à l’égard du modèle AIP d’imputabilité en éducation (Nagy, Demeris et van Barneveld, 2000). Des zones de congruence et de non‐congruence entre les plans et le modèle ont été identifiés. Les résultats donnent à penser que les plans de réussite faisaient une large place aux épreuves communes en tant que mesure du rendement scolaire et n’étaient pas congruents avec certains éléments clés du modèle d’imputabilité en éducation, notamment en ce qui a trait à l’utilisation de données indicatrices ou de renseignements sur les politiques. Mots clés : planification de l’éducation, rendement scolaire, épreuves communes, évaluation des élèves